Characteristics at haematoxylin and eosin staining of ruptures of the long head of the biceps tendon. Issue 8 (10th December 2007) - Longo, U G; Franceschi, F; Ruzzini, L; Rabitti, C; Morini, S; Maffulli, N; Denaro, V
Abstract : Objective: To examine the relative prevalence of histological changes that have been found to be associated with the process of tendinopathy in lesions of the tendon of the long head of the biceps brachii and to evaluate the reliability of histopathological evaluation of tendon tissue in lesions of the tendon of the long head of the biceps. Design: Tendon samples were taken from 51 patients (31 men, 20 women; mean age 63.2 years) who underwent arthroscopic release of the long head of the biceps tendon because of refractory biceps tendinopathy and from 5 male patients who died of cardiovascular events (mean age 69.6 years). Histological examination was performed using haematoxylin and eosin staining of sections, which were interpreted using a semiquantitative grading scale assessing fibre structure and arrangement, rounding of the nuclei, regional variations in cellularity, increased vascularity, decreased collagen staining and hyalinisation. Results: The mean (SD) pathological sum score of ruptured tendons was greater than that of control tendons (15.76 (3.11) vs 3.4 (1.9), p<0.001). Within each specific category of tendon abnormalities, the χ 2 test showed significant differences between the control and ruptured tendons; all the variables were significantly different (Mann–Whitney U test 0.05, p<0.001). Using the κ statistic, the agreement between the two readings ranged from 0.53 to 0.85. Conclusions: Unruptured tendons of the long head of the biceps, even at an advanced age and ruptured tendons of the long head of the biceps are clearly part of two distinct populations.